Role of Community-based Organisations in Promoting Democratic Local Governance at the Grassroots in Bangladesh. (July 2018) - Bhuiyan, Md. Imran Hossain; Hassan, S. M. Kamrul; Islam, Kazi Maruful
Democratic local governance (DLG) is often regarded as a necessary precondition for transforming lives and livelihoods of people living in the rural areas of developing countries. This article tries to answer how community-based organisations (CBOs) shape the way services are delivered by local government agencies in Bangladesh. Furthermore, the article explores how the community's, especially women's, demands and interests are being negotiated at local political institutions. In doing so, the research focuses on Union Parishad (UP) as the core institution of the local power structure and Kachukata Gram Unnayan Parishad (GUP) as the case of a women-led CBO. It has been observed that Kachukata GUP has evolved as a full-fledged CBO over the years and currently mobilises marginalised groups to establish their rights and access to various government and non-government organisations. In addition to ensuring gender-responsive governance, GUP is also creating space for participation and developing interactive relationship between the people and power at the grassroots in Bangladesh.